The Effect of Nanoparticles of Piper crocatum Leaves Ethanolic Extract on Liver Insulin Receptor Expression of Diabetic Rat’s Induced by Streptozotocin - Tri Wahyu Pangestiningsih; Citra Ayu Pramesti; Nusaibah Nuraniyati; Bambang Sutrisno; Agus Purnomo (Journal of Tropical Biodiversity and Biotechnology, 2022)
Diabetes mellitus is a disease related to hyperglycemia and insulin resistance that can lead to the outcome of chronic liver diseases such as nonalcoholic fatty liver disease (NAFLD). Red betel leaves are known as traditional plants that have anti-hyperglycemic potential. This study aimed to investigate the effect of ethanolic extract of red betel leaves nanoparticle (RbL-Nps) on the liver and hepatic insulin receptor’s (INSR) expression in diabetic rats. Thirty rats were included in this study and further divided into five groups containing six rats each. Group I (GI) comprised of the normal rats; while group II (GII), III (GIII), IV (GIV) and V (GV) comprised of diabetic rats induced by streptozotocin (STZ) at dose of 45 mg/kg bw and nicotinamide (NA) at dose of 110 mg/kg bw, intraperitoneally. Group I and II were treated with 0,5% Na-CMC orally.  Group III, IV and V were given the oral administration of RbL-Nps at the doses 30, 60, and 90 mg/kg bw diluted in 0,5% Na-CMC, respectively. All groups were treated once daily and subsequently euthanized after 28 days. Liver tissues were collected for immunohistochemistry method to see the INSR expression and haematoxylin-eosin (HE) staining. Result in this study revealed that INSR expression on the GI, GIII and GIV were significantly higher compared to that on the GII (p < 0.05). On the other hand, there were no significant differences on the INSR expression between GV and GII (p > 0.05). Histologically, liver tissues retrieved from GII showed severe vacuolic and necrotic hepatocytes with dilatated sinusoid. Mild vacuolic and necrotic hepatocytes were observed from GV. There were no pathological changes observed in the liver tissues retrieved from GI, GII, and GIV. We concluded that RbL-Nps improved the liver condition of diabetic rats at doses of 30 and 60 mg/kg bw, but not at doses of 90 mg/kg bw.